Strategi Perbankan Dalam Memaksimalkan Kinerja Pegawai Pada Konteks Penempatan Dan Kepuasan Kerja PT Bank Perkreditan Rakyat Sumatera Selatan - Arubina Bangsawan; Muhammad Deni; Tutik Pebrianti; Indah Mawarni (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2023)
This research aims to determine the effect of employee placement and job satisfaction on the individual performance of Bank BPR Sumsel employees (2023). The research design uses the causality method with Multiple Linear Regression data analysis techniques. The research object was 78 South Sumatra BPR Bank employees. The data collection method that the author uses in this research is by using a questionnaire which is carried out technically via Google Form (Online). The results of the research show that Employee Placement and Job Satisfaction have a positive and significant effect on the individual performance of Bank BPR Sumsel employees. Furthermore, between the two independent variables in this research, the variable that has a more dominant influence is the Employee Placement variable, namely 0.512 (Positive) on the Individual Performance variable, while the remaining variable is Job Satisfaction, which is 0.271 (Positive).